Artificial ionospheric modification: The Metal Oxide Space Cloud experiment. Issue 5 (3rd May 2017) - Caton, Ronald G.; Pedersen, Todd R.; Groves, Keith M.; Hines, Jack; Cannon, Paul S.; Jackson‐Booth, Natasha; Parris, Richard T.; Holmes, Jeffrey M.; Su, Yi‐Jiun; Mishin, Evgeny V.; Roddy, Patrick A.; Viggiano, Albert A.; et al.
Abstract: Clouds of vaporized samarium (Sm) were released during sounding rocket flights from the Reagan Test Site, Kwajalein Atoll in May 2013 as part of the Metal Oxide Space Cloud (MOSC) experiment. A network of ground‐based sensors observed the resulting clouds from five locations in the Republic of the Marshall Islands. Of primary interest was an examination of the extent to which a tailored radio frequency (RF) propagation environment could be generated through artificial ionospheric modification. The MOSC experiment consisted of launches near dusk on two separate evenings each releasing 6 kg of Sm vapor at altitudes near 170 km and 180 km. Localized plasma clouds were generated through a combination of photoionization and chemi‐ionization (Sm + O → SmO + + e – ) processes producing signatures visible in optical sensors, incoherent scatter radar, and in high‐frequency (HF) diagnostics. Here we present an overview of the experiment payloads, document the flight characteristics, and describe the experimental measurements conducted throughout the 2 week launch window. Multi‐instrument analysis including incoherent scatter observations, HF soundings, RF beacon measurements, and optical data provided the opportunity for a comprehensive characterization of the physical, spectral, and plasma density composition of the artificial plasma clouds as a function of space and time. A series of companion papers submitted along with this experimental overview provide more detail on the individual elements for interested readers. Key Points: An overview of the 2013 Metal Oxide Space Cloud (MOSC) sounding rocket experiment from Kwajalein Atoll A comprehensive diagnosis of artificial plasma clouds generated through release of samarium vapor in the upper atmosphere Artificial modification of the radio frequency propagation environment